POTENSI TINDAKAN PRAKTIK MONOPOLI DAN PENYALAHGUNAAN PENGUASAAN PASAR FASILITAS ESENSIAL SEKTOR PELABUHAN DARI PERSPEKTIF HUKUM PERSAINGAN USAHA: Potential Monopolistic Practices and Abuse of Market Power of Essential Facilties in the Port Sector: A Competition Law Perspective - Simanullang, Venty Elisa Margareth; Anggraini, Anna Maria Tri (AMICUS CURIAE, 2025)
Indonesia is the largest archipelago, which makes the port an essential means for mobilizing the infrastructure that supports the country's economic growth. The port sector, which is operated by state-owned enterprises, has the potential to maximize economic growth. However, in reality, there have been numerous instances of state-owned companies operating in the port sector violating business competition laws. It is thus imperative to comprehend the doctrine of essential facilities and the potential transgressions perpetrated by business actors who are state-owned enterprises. This research adheres to a descriptive normative methodology, utilizing secondary data. The findings indicate that the doctrine of essential facilities espouses the notion that essential facilities are crucial facilities that the state must facilitate and nurture to enable optimal economic activities benefiting the community. Essential facilities are established by state-owned enterprises (SOEs) as a means of implementing Article 33 of the 1945 Constitution of the Republic of Indonesia. In their operations within the port sector, SOEs are required to adhere to the standards set forth in Law Number 17 of 2008 concerning shipping. SOEs as business actors in carrying out their business activities must also pay attention to the principles and norms contained in Law Number 5 of 1999, especially the prohibition of monopolistic practices and market control so as to create healthy business competition.